2021
DOI: 10.1101/2021.05.10.21256644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinfection by the SARS-CoV-2 Gamma variant in blood donors in Manaus, Brazil

Abstract: The city of Manaus, north Brazil, was stricken by a severe epidemic of SARS-Cov-2 in March 2020, reaching a seroprevalence of 76% by October 2020. Nevertheless, in late November an abrupt increase in hospitalizations and deaths hit Manaus, causing higher number of deaths compared to the first epidemic wave. It has been hypothesized that virus lineages circulating in the second wave, namely the P.1 variant of concern first detected in early December in Manaus, could be better at evading immunity generated in re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…31 Such boosting will be particularly apparent with assays that are prone to waning, such as the Abbott NC and RBD IgG assays and pseudovirus RVPN assay. 32 Hence, different assays and different combinations of SARS-CoV-2 antibody assays will be needed to address the multiple important questions that are arising as the pandemic and mitigation strategies evolve. There is evolving appreciation of different applications or use cases for serological testing that will require different assays/algorithms for the next phase of COVID-19 pandemic response.…”
Section: Discussionmentioning
confidence: 99%
“…31 Such boosting will be particularly apparent with assays that are prone to waning, such as the Abbott NC and RBD IgG assays and pseudovirus RVPN assay. 32 Hence, different assays and different combinations of SARS-CoV-2 antibody assays will be needed to address the multiple important questions that are arising as the pandemic and mitigation strategies evolve. There is evolving appreciation of different applications or use cases for serological testing that will require different assays/algorithms for the next phase of COVID-19 pandemic response.…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical models of infectious diseases have been playing a pivotal role in understanding emerging and re-emerging infectious disease outbreaks, evaluating strategies for effective prevention and control measures, as well as providing suggestions to policymakers on how to effectively control the epidemics in a timely fashion. In this paper, we develop a simple conceptual model to qualitatively reproduce the observed dynamics of SARS-CoV-2 in Manaus with reinfection [9]. The model was able to capture the observed dynamics on reinfection by a new variant [9,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Prete et al [9] studied the antibody level (IgG) of 238 repeated blood donors in Manaus, and found that some of them showed evidence of being infected with a wild strain in the first wave, i.e., an increase in their IgG level in April-May 2020. Others showed evidence of being infected with the P.1 strain in the second wave, i.e., elevated IgG levels from December 2020 to January 2021.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations